Solid Waste Mixtures as Constructed Wetlands Filling: Effect of Hydraulic Loading Rate on Nutrient Removal from Wastewater - Pinho, Henrique J. O. (2018)
This study aims to contribute to constructed wetlands’ (CWs) eco-efficiency by applying the concepts of circular economy and waste to treat waste. Five sets of lab-scale CWs with different combinations of filling materials were evaluated and the effect of the hydraulic loading rate (HLR) on the nutrient removal efficiencies was studied. Each CW set consisted of two, duplicate, plastic pots with solid waste filling supporting Phragmites australis macrophyte plants. The filling materials were layer combinations of limestone rock fragments, a waste from construction activities, and one of four other solid wastes: cork granulates from the cork industry (LCG); snail shells from the food and catering industry (LSS); coal slag from coal power plants (LCS); and clay brick fragments from construction activities (LBF). A reference set (LO) was filled only with limestone fragments. The CWs were operated using a low-strength wastewater in successive fill-and-drain cycles with a retention time of one to eight days and a one-day rest. Their removal efficiency was evaluated for COD, total phosphorus (TP) and total nitrogen (TN). All four CWs with mixed filling showed COD removal efficiencies higher than the reference CW and above 79%. The highest removal efficiency was achieved by the LCS CW (91 to 97%). The reference LO CW showed the highest TP removal efficiency. With exception of the LSS CW, the mixed filling CWs showed removal efficiencies close to the reference CW (above 55%). All but the LSS CW showed higher TN removal efficiencies than the reference CW (above 51%). The observed effect of HLR depends on the type of CW. The effect on COD, TP and TN removal efficiencies averaged 9%, 15% and 20%, respectively, for a range of HLR from 0.005 to 0.087 m/day. From this study it can be concluded that all tested layer-packed mixed solid waste fillings are adequate substrate combinations for nutrient removal from wastewater. Moreover, high nutrient removal efficiencies were maintained over a wide range of hydraulic loading rates. This innovative combination of waste materials can improve the CW adaptability to specific types of wastewater and contribute to reducing solid waste disposal in landfills.